(untitled) (Journal of the College of Basic Education, 2022)
Time is an essential variable in human life, and this exceptionality revolves around time with its limits, which God made it a secret that no one knows except Him. The fifth verse of Surat Al-Hajj confirms this fact (and we settle in the wombs whatever we want for an appointed time). Or store it, and that is why it was said that time is like a sword, if you do not cut it, it will cut you.